THE RELATIONSHIP OF THE ROLES OF BOTH CIVIL AND PRIVATE SOCIETY TOWARDS THE INDONESIAN GOVERNMENT THAT PRACTISES DESENTRALISED DEMOCRACY TO ACHIEVE GOOD GOVERNANCE - Hidayatulloh, Dadan; Suwaryo, Utang; Sulaeman, Affan; Deliarnoor, Nandang Alamsah (Advances in Social Sciences Research Journal, 2018)
In a democratic country, civil society will develop and grow strongly. The state as an integration of political power, is the main organization of political power. Also, the state is a tool of society that has the power to regulate human relations in society and regulate the symptoms in society. Good governance can also be interpreted as a synergic and constructive relationship between the state, the private and the civil society. This study aims to find out and understand how is the relationship of the roles of both civil and private society in order to achieve good governance. In this research applied the civil society, state theory, the concept of good governance, and the concept of decentralization theory. The results that the relationship of the roles, both civil and private society can be seen through building democratic governance through the role of civil society, social and political participation in decentralization. Local governments in Indonesia, through a decentralized system, have enabled the rapid development of democracy. Thus, democratic governance depends on how much civic engagements are.